The Consulate General of the Republic of Poland in Sydney – the Activities, Tasks and Responsibilities - Kończyk, Monika (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The Consulate General of the Republic of Poland in Sydney is one of the thirty-seven consulates that function in Australia. The scope of duties and work of the consulate is set up by the rules and directives of the Polish Foreign Policy Strategy for 2017–2021 and is determined by the Consular Law and other regulations.